Blue Light Exposure, Sleep Quality, And Eye Strain: Interkoneksi Penggunaan Gadget dan Kesehatan Mata Mahasiswa Kedokteran - Dio Pratama; Jedo Muchamad Tias Temun; Zahratu Ayu Rachmanita (Lembaga Pengembangan Kinerja Dosen, 2025)
The increasing use of gadgets among medical students raises concerns about the health impacts, especially on sleep quality and eye health. Medical students have a high intensity of digital device use due to academic demands, which has the potential to cause excessive exposure to blue light (blue light), sleep disturbances, and eye fatigue (eye strain). This study aims to explore the relationship between the duration of gadget use with sleep quality and eye strain in medical students and to understand the factors that strengthen or weaken its impact. The research method used is qualitative descriptive based on a literature study by reviewing literature from scientific journals, books, and relevant documents. The results of the study showed that exposure to blue light can reduce melatonin production, disrupt circadian rhythms, and cause sleep disorders such as insomnia. In addition, long-term use of gadgets without sufficient rest increases the risk of digital eye strain, characterized by symptoms such as dry eyes, blurring, pain, and headaches. Medical students who are susceptible to intensive exposure to digital screens are at higher risk of this disorder. In conclusion, there is a strong interconnection between gadget use, sleep quality, and eye fatigue. Preventive efforts such as screen time management, use of blue light filters, and education about healthy visual habits are important to maintain the health and productivity of medical students.